Human Development and Controlled Substance Prescribing in Ohio Counties - Patricia Factor; Wallace Chambers; JoAnna “Anna” C. S. Kauffman; Tunu Kinebrew; Natasha Yonley; Ross M. Kauffman (Ohio Journal of Public Health, 2019)
Background: Human development is a holistic measure of well-being. The American Human Development Index (AHDI) operationalizes the concept for the American context, using a composite measure of income, education, and health. This work presents the first county-level examination of AHDI for the state of Ohio and examines the relationship between human development and controlled substance prescribing. Methods: Publicly available data from the census and prior publications were compiled to calculate county-level AHDI for all 88 Ohio counties. Correlations were examined between AHDI and 4 classes of controlled substances, opioids, benzodiazepines, stimulants, and sedatives, using Pearson product moment correlation coefficient. Results: County AHDI scores ranged from 3.3 to 7.6, with mean and median values of 4.8. At the county level, human development is negatively correlated with opioid (r = -0.46, r2 = 0.22, P <0.0001) and benzodiazepine (r = -0.43, r2 = 0.18, P <0.0001) prescribing and positively associated with stimulant prescribing (r = 0.49, r2 = 0.24, P <0.0001). Neither sedative prescribing practices (r = 0.09, P = 0.40) nor median age (r = -0.09, P = 0.41) were significantly correlated with AHDI. Conclusion: There is a strong correlation between AHDI and prescribing of several classes of controlled substanc-es. Work remains to ascertain mechanisms and directionality of these relationships. Whether higher prescribing in areas with lower human development is an attempt to medicate health inequity or low human development is an additional manifestation of the opioid epidemic, this study underscores the necessity of pursuing equity in all policies.
Keywords: Opioids; controlled substances; Prescribing; Human development; Human development index